Case studies in Public Housing: Sabah - Dullah Mulok; Siti Hajar Samsu (Cagamas Holding Berhad, 2013)
Meeting housing needs is a major national social objective, particularly in a less-developed state such as Sabah. This objective is to ensure that all people in the state, particularly the lower-income group regardless of ethnicity, can afford to have a suitable place to live in. Major land schemes and the systematic implementation of public housing in the state are emphasised to improve living conditions of the population not only in rural but also in urban areas. The Government’s emphasis is on housing for the low-income group and the thrust of public housing programmes is to bring housing within the means of the poor. The state government understands that the lack of affordable housing can lead to negative effects on the overall population and the community's overall wellbeing.